PERKEMBANGAN PEDOMAN TEKNIS PENGOLAHAN BAHAN PERPUSTAKAAN : KAJIAN DOKUMEN TENTANG PEDOMAN PENGOLAHAN BAHAN PERPUSTAKAAN YANG PERNAH DITERBITKAN OLEH PERPUSTAKAAN NASIONAL - Sri Mulyani (Ikatan Pustakawan Indonesia, 2017)
Library materials processing is an intelectual activity that organize various sources of information with the standard rules that apply intenationally and nationally to provide information retrieval tools which can be used by users. To obtain the search tool as an outcome of these activities, it is necessary to provide technical guidance as a working guide to manifest uniformity in processing of library materials. The study of library materials processing guidelines aim to detemined development of publication of various technical guidelines of library materials processing ever published by National Library of Indonesia. This study is expected to provide an overview of the development publication of technical guidelines for library materails processing. This study use descriptive methode and document study for data collection, by collecting the publication of library materials processing guidelines published by the National Library since 1982 until 2016.